CHEST PAIN IN THE EMERGENCY ROOM: IDENTIFICATION, CLASSIFICATION AND MANAGEMENT OF ACUTE CORONARY SYNDROME (International Seven Journal of Multidisciplinary, 2025)
Chest pain is one of the most common complaints in emergency departments, and can be classified as cardiac and non-cardiac in origin. When of cardiac origin, it can indicate highly serious and life-threatening conditions such as Acute Coronary Syndrome (ACS) and pulmonary thromboembolism. Cardiovascular diseases are the leading cause of death in the world and represent the leading cause of death in Brazil since 1960. According to the World Health Organization (WHO), in 2019, 18 million deaths were due to cardiovascular diseases in the world. Among the main causes of death from cardiovascular diseases, ischemic heart disease stands out, which represents the cause of 9 million deaths in the same year. According to DATASUS, in 2021 in Brazil, approximately 115,000 deaths from ischemic heart disease were described, reflecting the global scenario. Its etiology is multifactorial, but it is worth noting that the disease is closely related to preventive risk factors, such as smoking, obesity, poor diet, sedentary lifestyle, and poor control of underlying diseases such as hypertension and diabetes. The result of these poor lifestyle habits is high morbidity and mortality and increasing socioeconomic impact since the management of this comorbidity represents 8.3% of all hospitalizations and 18% of SUS costs according to DATASUS in 2022. Given this scenario, it is essential to implement strategies aimed at changing lifestyle habits, in addition to emphasizing early diagnosis, appropriate classification, and efficient management of patients, to reduce morbidity and mortality associated with cardiovascular diseases.